2021
DOI: 10.3390/antibiotics10060647
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Antibiotic Supply without a Prescription for Common Infections: A Cross-Sectional National Survey in Sri Lanka

Abstract: Inappropriate antibiotic use is a problem in Sri Lanka. We investigated pharmacy staff’s attitudes towards antibiotic supply for common infections in Sri Lanka. A self-reported cross-sectional survey was conducted among a random sample (n = 369) of pharmacies. We assessed staff’s beliefs and attitudes to antibiotic supplying for common infections (common cold and cough, sore throat, diarrhoea, wound and urinary tract infections (UTI)). Pharmacists (n = 210; 79%) and pharmacy assistants (n = 55: 21%) responded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The results demonstrate that the purchase of antibiotics without a prescription is still common practice across Vietnam despite current regulations (81.7% of participants stated they would still purchase antibiotics without a prescription). These findings were similar or higher than recent results in China (45.5–88.4%) [ 17 , 45 ], Cameroon (47%) [ 46 ] and earlier in Saudi Arabia (48.4–70.7%) before greater enforcement of the laws and fines [ 28 , 47 ] as well as Sri Lanka (30.2%) [ 29 ]. However, our results show appreciably greater dispensing of antibiotics without a prescription in Vietnam than seen in Saudi Arabia following enforcement of their regulations coupled with appreciable fines for abuse [ 28 ], and in the Republic of Srpska [ 43 ] ( Table 1 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results demonstrate that the purchase of antibiotics without a prescription is still common practice across Vietnam despite current regulations (81.7% of participants stated they would still purchase antibiotics without a prescription). These findings were similar or higher than recent results in China (45.5–88.4%) [ 17 , 45 ], Cameroon (47%) [ 46 ] and earlier in Saudi Arabia (48.4–70.7%) before greater enforcement of the laws and fines [ 28 , 47 ] as well as Sri Lanka (30.2%) [ 29 ]. However, our results show appreciably greater dispensing of antibiotics without a prescription in Vietnam than seen in Saudi Arabia following enforcement of their regulations coupled with appreciable fines for abuse [ 28 ], and in the Republic of Srpska [ 43 ] ( Table 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…Antibiotics were mainly purchased to treat RTIs (61.4%), similar to findings across countries including China (45.5%), Saudi Arabia in 2018 prior to recent initiatives and Sri Lanka [ 11 , 29 , 45 , 47 ]. As seen, the main respiratory-related symptoms for which antibiotics were dispensed were flu-like symptoms, coughs and colds.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous self-reported surveys and qualitative studies have shown that self-medication with antibiotics is common, and that antibiotic supply by private pharmacies in Vietnam is frequently inappropriate. 25 , 26 , 27 Limitations of previous research include a lack of blinding of the pharmacists – potentially contributing to social desirability bias 28 – as well as possible recall bias. 29 Standardised patient surveys (SPS) can overcome these forms of bias, by evaluating the performance of pharmacy staff in real life scenario.…”
Section: Introductionmentioning
confidence: 99%